Not Mere Lexicographic Cosmetics: The Compilation and Structural Features of Isichazamazwi SezoMculo - Nobuhle Moyo (Lexikos, 2011)
Abstract: This article offers a brief overview of the compilation of the Ndebele music terms dictionary, Isichazamazwi SezoMculo (henceforth the ISM), paying particular attention to its structural features. It empha-sises that the reference needs of the users as well as their reference skills should be given a determining role in all lexicographic decisions leading to the publication of a dictionary. Dictionary structure should, there-fore, be conceived and evaluated in terms of its data constituents and the accessibility of these data. Accord-ingly, this article demonstrates that the structure of the ISM is not a case of mere cosmetics but a lexico-graphic mode of communication between the dictionary compilers and users who are participants in a lexi-cographic communication process. In this way, the article highlights some of the challenges encountered during the compilation of the ISM and the strategies the compilers employed to facilitate the communication process between the lexicographers and the users regarding dictionary contents and the arrangement thereof. From such a perspective, this article may provide useful insights for LSP lexicography in African languages, prospects of which are based on the increased need for knowledge acquisition and dissemination as well as the multilingual nature of African societies.